Genome-enabled studies of anaerobic, nitrate-dependent iron oxidation in the chemolithoautotrophic bacterium Thiobacillus denitrificans - Beller, Harry R.; Zhou, Peng; Legler, Tina C.; Chakicherla, Anu; Kane, Staci; Letain, Tracy E.; O'Day, Peggy A. (Frontiers in Microbiology, 2013)
Thiobacillus denitrificans is a chemolithoautotrophic bacterium capable of anaerobic, nitrate-dependent U(IV) and Fe(II) oxidation, both of which can strongly influence the long-term efficacy of in situ reductive immobilization of uranium in contaminated aquifers. We previously identified two c-type cytochromes involved in nitrate-dependent U(IV) oxidation in T. denitrificans and hypothesized that c-type cytochromes would also catalyze Fe(II) oxidation, as they have been found to play this role in anaerobic phototrophic Fe(II)-oxidizing bacteria. Here we report on efforts to identify genes associated with nitrate-dependent Fe(II) oxidation, namely (a) whole-genome transcriptional studies [using FeCO3, Fe2+, and U(IV) oxides as electron donors under denitrifying conditions], (b) Fe(II) oxidation assays performed with knockout mutants targeting primarily highly expressed or upregulated c-type cytochromes, and (c) random transposon-mutagenesis studies with screening for Fe(II) oxidation. Assays of mutants for 26 target genes, most of which were c-type cytochromes, indicated that none of the mutants tested were significantly defective in nitrate-dependent Fe(II) oxidation. The non-defective mutants included the c1-cytochrome subunit of the cytochrome bc1 complex (complex III), which has relevance to a previously proposed role for this complex in nitrate-dependent Fe(II) oxidation and to current concepts of reverse electron transfer. A transposon mutant with a disrupted gene associated with NADH:ubiquinone oxidoreductase (complex I) was 35% defective relative to the wild-type strain; this strain was similarly defective in nitrate reduction with thiosulfate as the electron donor. Overall, our results indicate that nitrate-dependent Fe(II) oxidation in T. denitrificans is not catalyzed by the same c-type cytochromes involved in U(IV) oxidation, nor have other c-type cytochromes yet been implicated in the process.